Forest and landscape restoration severely constrained by a lack of attention to the quantity and quality of tree seed: insights from a global survey - CGIAR Research Program on Forests, Trees and Agroforestry (2018)
Two papers published by the flagship in 2017/2018 (Jalonen et al. 2017/2018), and (Roshetko et al. 2017/2018) were the first studies to verify and document a common and often quoted suspicion that many plantings and regenerations for restoration and/or conservation do not pay adequate attention to the genetic quality of the reproductive material. This is one of the most important factors of success for the huge global agenda of forest landscape restoration with very significant implications for conservation of biodiversity